Bioinformatics Education in Greece: A Survey - Efrosyni-Alkisti Paraskevopoulou-Kollia; Pantelis G Bagos (Biosaintifika: Journal of Biology & Biology Education, 2017)
Bioinformatics is an interdisciplinary field, placed at the interface of Biology, Mathematics and Computer Science. In this work, we tried for the first time to investigate the current situation of Bioinformatics education in Greece. We searched the online resources of all relevant University Departments for Bioinformatics or relevant courses. We found that all the Departments of Biological Sciences include in their curricula courses dedicated to Bioinformatics, but this is not the case for Departments of Computer Science, Computer Engineering, or Medical Schools. Despite the fact that large Universities played a crucial role in establishing Bioinformatics research and education in Greece, we observe that Universities of the periphery invest in the field, by including more relevant courses in the curricula and appointing faculty members trained in the field. In order for us to “triangulate” we didn’t confine ourselves to online resources and descriptive statistics but we also included interviews so as to have a more spherical view of the subject under discussion. The interviews provided useful insights regarding the teaching methods used by bioinformatics tutors, their attitudes and the difficulties they encounter. The tutors mentioned also the material that they choose, the audience’s attraction techniques and the feedback they receive.